1996
DOI: 10.1074/jbc.271.13.7522
|View full text |Cite
|
Sign up to set email alerts
|

A New α-Conotoxin Which Targets α3β2 Nicotinic Acetylcholine Receptors

Abstract: We have isolated a 16-amino acid peptide from the venom of the marine snail Conus magus which potently blocks nicotinic acetylcholine receptors (nAChRs) composed of alpha3beta2 subunits. This peptide, named alpha-conotoxin MII, was identified by electrophysiologically screening venom fractions against cloned nicotinic receptors expressed in Xenopus oocytes. The peptide's structure, which has been confirmed by mass spectrometry and total chemical synthesis, differs significantly from those of all previously iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
516
2
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 468 publications
(535 citation statements)
references
References 32 publications
16
516
2
1
Order By: Relevance
“…Thus, nAChRs containing the ␣7 subunit do not appear to be required for wave generation. On the other hand, ␣-conotoxin-MII and ␣-conotoxin-AU1B, toxins that preferentially block ␣3␤2 and ␣3␤4 nAChRs, respectively (Cartier et al, 1996;Luo et al, 1998), dramatically reduced wave frequency. These findings indicate that the functional nAChR receptors mediating waves contain ␣3, ␤2, and ␤4 subunits.…”
Section: Nachr-mediated Retinal Wavesmentioning
confidence: 96%
“…Thus, nAChRs containing the ␣7 subunit do not appear to be required for wave generation. On the other hand, ␣-conotoxin-MII and ␣-conotoxin-AU1B, toxins that preferentially block ␣3␤2 and ␣3␤4 nAChRs, respectively (Cartier et al, 1996;Luo et al, 1998), dramatically reduced wave frequency. These findings indicate that the functional nAChR receptors mediating waves contain ␣3, ␤2, and ␤4 subunits.…”
Section: Nachr-mediated Retinal Wavesmentioning
confidence: 96%
“…The α-conotoxins Vc1.1, AuIB and MII were synthesised as previously described (Schnolzer et al 1992;Cartier et al 1996;Luo et al 1998;Clark et al 2006). Briefly, Boc solid phase chemistry was used to synthesise, deprotect and cleave from the resin all peptides as described (Schnolzer et al 1992).…”
mentioning
confidence: 99%
“…These conclusions were conclusively confirmed by the finding that deleting the α7 subunit resulted in elimination of the [ 125 I]-α-bungarotoxin binding site [70] and that null mutation of either the α4 [71] [73,75,76,77,78,79] demonstrating that what is routinely referred to as high affinity nicotine binding sites should be referred to as high affinity agonist binding sites. A little more than 10 years ago, two new high affinity ligands were introduced to the field, radiolabeled epibatidine [80,81] and α-conotoxin MII (α-CtxMII) [82,83]. [ 3 H]-Epibatidine was originally described as being a very high affinity ligand that was useful, principally, for measuring α4β2* nAChRs [80,81] (* indicates possible additional subunits).…”
mentioning
confidence: 99%
“…Expression of nAChRs in Xenopus laevis has shown that α-CtxMII binds with high affinity to α3β2* nAChRs [82] and α6β2* nAChRs [33]. However, deletion of nAChR subunits clearly demonstrated that α6 is required to form those nAChRs that bind 125 I]-α-CtxMII with high affinity in dopaminergic neurons whereas α3 is not.…”
mentioning
confidence: 99%